2016
DOI: 10.17219/acem/41860
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of Selective Activation of Retinoic Acid Receptors on Bone Metabolism and Bone Mechanical Properties in Rats

Abstract: hibitors, androgen deprivation therapy, heparin, calcineurin inhibitors and some chemotherapies are among the drugs increasing the risk of osteoporotic fractures [1].The mechanisms of the regulation of bone turnover involved in the etiology and pathology of osteoporosis seem to be very complex. Recent papers have revealed that various nuclear receptors are involved in the regulation of bone metabolism, its physiology and pathology. Many studies suggest Osteoporosis is defined as pathological bone microarchitec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Recently, rats receiving intragastrically tazarotene (0.075 mg/kg) in sesame oil (4 ml/kg) daily were demonstrated to have worse bone mechanical properties than control animals. Both mean Young’s modulus and the stiffness were significantly impaired at the femur in tazarotene-treated rats suggesting osteoporotic nature of the drug [29]. Previously, Hotchkiss et al also demonstrated an unfavorable effect of retinoids in long bones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, rats receiving intragastrically tazarotene (0.075 mg/kg) in sesame oil (4 ml/kg) daily were demonstrated to have worse bone mechanical properties than control animals. Both mean Young’s modulus and the stiffness were significantly impaired at the femur in tazarotene-treated rats suggesting osteoporotic nature of the drug [29]. Previously, Hotchkiss et al also demonstrated an unfavorable effect of retinoids in long bones.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced bone resorption was manifested by a significant increase in serum tartrate-resistant acid phosphatase in the study of Saadi et al [21], whereas other markers (serum pyridinoline, urine deoxypyridinoline, urine hydroxyproline) were elevated insignificantly [19, 20, 22, 29]. Surprisingly, Trifiro and Norbiato found even a decrease in urine N-terminal telopeptide of type I collagen (NTx) level on isotretinoin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Although a large effect size, given the precision with which Young's modulus is estimated, such a difference corresponds to ~10.5% difference in means. A recent article found a 24% difference in Young's modulus between groups when testing drug effects on Young's modulus ( Nowak et al, 2016 ). Since we have power to detect a difference less than half their observed difference and a 10.5% difference in Young's modulus would be clinically meaningful, our study design with eight groups and N = 5/group was justified.…”
Section: Methodsmentioning
confidence: 99%